Healthy food access and policy: a study of rural and urban food environments in Riley County, Kansas - Stensland, Alexsis (Kansas State University, 2015)
Accessing healthy food can be a challenge for people living in both rural and urban environments. A broad range of factors influences one’s food security, including the accessibility and affordability of food retailers, travel time to shopping, availability of healthy foods, and food prices. The connections between planning and food systems have begun to emerge and be examined but planners face many barriers when tackling food system issues that range from turf problems, a lack of knowledge that any problem exists, to a lack of funds. The study purposes were to 1) identify areas with low access to healthy food sources; 2) discover barriers and perceptions of healthy food accessibility among community members; and 3) explore current planning policies and practices for increasing healthy food accessibility. The study area of this case is Riley County, Kansas, which has lower food accessibility especially to health foods in low income areas located in urban neighborhoods, even though rural areas are further away from a healthy food store. The research has the potential to inform the local food system framework and provide guidance for local policy makers and stakeholder groups. Surveys were collected from 150 households in order to identify challenges and barriers respondents face when obtaining healthy food. Food prices and low income were the largest barriers survey respondents faced when obtaining healthy food. Interviews conducted among 6 individuals from planning offices, market, and community stakeholder groups and both urban and rural issues were discussed. Currently, there is understanding of the importance of healthy food but little action that follows. There are opportunities for planners and policy makers to get involved with planning for the local food system. Partnerships must be established to share resources and technical skills among stakeholders in order to plan for healthy community food systems.
Keywords: Healthy food access; Community food system; planning and policy; Riley County, Kansas; Rural planning; Public Health (0573)